Apresentação - Tavares, Márcia Santana; Zucco, Maise Caroline; Delgado, Josimara; Freire de Lima e Souza, Ângela Maria; Bacellar Sardenberg, Cecilia Maria; Costa Pinheiro, Clarice (Revista Feminismos, 2020)
Apresentação da primeira edição do ano de 2019.